A prospective study on risk assessment and prophylaxis of venous thromboembolism in general surgery patients - Nita Bharti; Anil Luther; Michael Deodhar; Amit Mahajan; Rajesh Kumar (Journal of Family Medicine and Primary Care, 2024)
Aims and Objective: To evaluate the patients at risk of venous thromboembolism (VTE) based on Caprini VTE risk assessment scale and the effect of implementation of this scale on the use of thromboprophylaxis. Materials and Methods: A prospective study was conducted, including patients who underwent major elective surgical procedures. Demographic details were noted, and VTE prophylaxis offered if needed. According to the VTE risk assessment scale, patients were categorised into very low-, low-, moderate-, and high-risk categories. The data were analysed statistically. Results: A total of 500 patients (women = 259; men = 241) were enrolled in this study. Of them, eight women and nine men developed VTE (P = 0.691). The maximum number of patients who developed VTE belonged to 61–70 years group (n = 7). According to VTE risk assessment, 61 patients were categorised as low-risk, 217 patients as moderate-risk, and 222 patients were categorised as high-risk. A significant (P < 0.0005) correlation was found between body mass index (BMI) and VTE development. In obese patients with BMI >25, 14 patients developed VTE. Out of total, 329 patients received prophylaxis for deep vein thrombosis. Of 284 patients who received pharmacologic prophylaxis, only three developed VTE (P = 0.002). Of 145 patients who received mechanical prophylaxis, 75 had high risk and none of them developed VTE. Four patients had mortality, and a significant (P = 0.022) correlation was found between mortality and VTE development. Conclusion: According to Caprini risk assessment scale, the prophylaxis for VTE was effective in patients undergoing major elective general surgery, resulting in significant lowering of morbidity and mortality.